Addressing planetary health challenges in Africa. Issue 1 (December 2016) - Ezeh, Alex
Abstract Drawing on the report of the Rockefeller Foundation-Lancet Commission on planetary health—Safeguarding human health in the Anthropocene epoch, this piece presents a discussion of the implications of the report's findings and conclusions for Africa. It explores the key planetary health challenges facing Africa and what Africa can do to address them. In addition to highlighting current and future trajectories of key environmental changes in Africa and their implications for health and well-being, this transcript from the 21st Conference of Parties (COP21) side event, "Healthy Lives on a Healthy Planet", identifies a set of priority action Africa needs to take in order to deal with these challenges. It ends with reflections and key recommendations from participants at the regional launch of the report in Nairobi, Kenya, in October 2015.